Addressing the challenges of interaction in online language courses. (December 2021) - Harsch, Claudia; Müller-Karabil, Anika; Buchminskaia, Ekaterina
Abstract: The Covid pandemic enforced a rapid transition to online delivery of language courses worldwide, a different situation from carefully planned online courses. Our paper contributes to shedding light on the mechanisms and challenges of online language learning under emergency circumstances. We draw on evaluation data of the Covid semester in spring 2020 at a large languages centre in Germany, where 69 teachers were forced to deliver 224 language courses for over 2400 students online with no preparation time. All were invited to an evaluation, where 35 teachers and 898 students reported challenges of this rapid transition and responses to overcome these. The mixed-methods analysis revealed that one major challenge lay in creating learning-conducive interaction, the reasons for which are rooted mainly in unclear expectations regarding the new roles of teachers and students, insufficient social presence and inappropriate communication channels and settings. Our findings have implications also beyond the pandemic, as they reveal promising responses towards overcoming these challenges. Most importantly, they point towards the potential of a collaborative effort between teachers and students with the aim of creating innovative meeting spaces, choosing appropriate communication channels and designing synchronous activities that are conducive to stimulating meaningful interaction and fostering social presence.